Fabrication of Embedded Microstructures Via Lamination of Thick Gel‐Casted Ceramic Layers. Issue 2 (18th January 2013) - Cheah, Kean How; Chin, Jit Kai
<x xml:space="preserve">Abstract</x> This article describes a new approach to fabricate various embedded ceramic microstructures. Design geometries of the microstructures are replicated onto a soft reusable polydimethylsiloxane (PDMS) mold. Rapid consolidation of ceramic suspension on the molds using gel‐casting technique produces structured ceramic layers. 85% aqueous glycerol solution has been identified as suitable adhesive agent to laminate the ceramic layers. Capability of the approach in fabricating embedded microstructures of 3‐dimensional and aspect ratio as high as 20 and 50 has been demonstrated. Ceramic microthruster and Y‐shaped microfluidic reactor are fabricated using this new approach to show its potential to construct various ceramic microdevices.